ANALISIS STRATEGI PENGEMBANGAN INDUSTRI KECIL PAKAIAN JADI DENGAN PENDEKATAN CONTINGENT STRATEGIC SUCCESS FORMULA - Baroto, Teguh (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
Companies that are categorized as small industries face many difficulties to keep survive or to develop their products. The subject of this study was convection home industry with the commodity as follows: Muslim clothes, sport shirt, baby clothes, children clothes, bed covers, veils, and many kinds of embroidery products. The purpose of CSSF (Contingent Strategic Success Formula) approach was to analyze the formula of success strategy by combining the internal condition with external condition of the company. The ways to do that were by measuring, estimating, and predicting the environment condition of the company at this time and at the specific time in the future. The measuring of internal condition of the company is aimed to know the things that need to be repaired so the company can fulfill the requirement of optimal external condition in the future. The finding of this study was shown in 4 cases. First, the variables that have influence in convection home industry were 36 industries. Second, there were 3 clusters of convection home industries, those were: Cluster 1, the companies of embroidery convection that lack of success, and Cluster 2 and 3, the company with mass production that success enough and very success. Cluster 1 was categorized as the company that left behind in the competition and its agresivieness and responssiveness is under environment turbulence. Cluster 2 was success enough because the turbulence difference with agresiveness and responssiveness is not wide. Cluster 3 was the best one because the company was number one in the competition and its agresiveness and resposiveness exceed the environment turbulence at this time. Three, to get success in the future, the company need to fulfill the optimal internal condition that suitable with the level of turbulency. It is better for the companies to apply 3 succeed marketing points, those are: to develop the positioning of the products in the specific SBA, create the strong differences, create mark equities, or the emotional relationship with the customers